Post-licensure safety surveillance of zoster vaccine live (Zostavax®) in the United States, Vaccine Adverse Event Reporting System (VAERS), 2006-2015 - Elaine R. Miller; Paige Lewis; Tom T. Shimabukuro; John Su; Pedro Moro; Emily Jane Woo; Christopher Jankosky; Maria Cano (Taylor & Francis Group, 2018)
Background: Herpes zoster (HZ), or shingles, is caused by reactivation of varicella-zoster virus in latently infected individuals. Live-attenuated HZ vaccine (zoster vaccine live, ZVL) is approved in the United States for persons aged ≥50 years and recommended by the CDC for persons ≥60 years. Methods: We analyzed U.S. reports of adverse events (AEs) following ZVL submitted to the Vaccine Adverse Event Reporting System (VAERS), a spontaneous reporting system to monitor vaccine safety, for persons vaccinated May 1, 2006, through January 31, 2015. We conducted descriptive analysis, clinical reviews of reports with selected pre-specified conditions, and empirical Bayesian data mining. Results: VAERS received 23,092 reports following ZVL, of which 22,120 (96%) were classified as non-serious. Of reports where age was documented (n = 18,817), 83% were in persons aged ≥60 years. Reporting rates of AEs were 106 and 4.4 per 100,000 ZVL doses distributed for all reports and serious reports, respectively. When ZVL was administered alone among persons aged ≥50 years, injection site erythema (27%), HZ (17%), injection site swelling (17%), and rash (14%) were the most commonly reported symptoms among non-serious reports; HZ (29%), pain (18%), and rash (16%) were the most commonly reported symptoms among serious reports. Six reports included laboratory evidence of vaccine-strain varicella-zoster virus (Oka/Merck strain) infection; AEs included HZ, HZ- or varicella-like illness, and local reaction with vesicles. In our review of reports of death with sufficient information to determine cause (n = 46, median age 75 years), the most common causes were heart disease (n = 28), sepsis (n = 4), and stroke (n = 3). Empirical Bayesian data mining did not detect new or unexpected safety signals. Conclusions: Findings from our safety review of ZVL are consistent with those from pre-licensure clinical trials and other post-licensure assessments. Transient injection-site reactions, HZ, and rashes were most frequently reported to VAERS following ZVL. Overall, our results are reassuring regarding the safety of ZVL.